Estonia, the new EU economy. Building a Baltic miracle? - Hannula, Helena; Radosevic, Slavo; von Tunzelmann, Nick (Aldershot, 2006)
"Estonia is regarded by many as one of the most hopeful cases for the integration of Eastern Europe into the enlarged European Union. It provides positive examples of how the integration process can be well handled, but at the same time some of the contentious issues that can arise. This book assesses the tensions involved in the development of the Estonian economy in terms of growth, convergence, financial development, labour reallocation, structural and organizational change, and the role of foreign companies and international networks. The analysis of Estonia is placed within a broader context and among a wider set of nations and thus aims at understanding the potential for growth and structural change in the eastern part of the enlarged EU. In these and related fields, the book seeks to draw lessons from Estonia for other new (and indeed future) EU accession countries."